Epistemological effects of the political on relativistic political geography - ehsan Lashgari Tafreshi (تحقیقات کاربردی علوم جغرافیایی)
In the classical view, the political dimension study of space has always been considered as the political geography ontological basic. Gradually from the 1980s with the development of post-positivist perspectives on human geography; Politics affected all social spheres from government and political parties to gender and considered the smallest power relations associated with the political concept. The political issue has rejected the organization of space on the basis of formal logic and has introduced new forms of epistemological reconstruction in the study of the relationship between politics and space. In this article, has been attempted to explain the political epistemological consequences in the study of relationship between politics and space. Research findings indicate that political dimension of space study is needed epistemic relativism in context of the political. In this regard, intersubjective cognition has a special dependence on the historical evolution of space and therefore requires to power factor genealogy. This spatial genealogy is always linked to the conflict that exists in human societies and forms the possibility of space antagonistic cognition. In this regard, the social meaning of geographical space; considered as place of conflict and resistance of marginalized groups and hegemonic forces in society Which reach a kind of adaptive balance within a certain time.  This process is caused, the epistemological model adaptation of cultural geography and political geography with each other.